French experience of balloon pulmonary angioplasty for chronic thromboembolic pulmonary hypertension. Issue 5 (18th May 2019) - Brenot, Philippe; Jaïs, Xavier; Taniguchi, Yu; Garcia Alonso, Carlos; Gerardin, Benoit; Mussot, Sacha; Mercier, Olaf; Fabre, Dominique; Parent, Florence; Jevnikar, Mitja; Montani, David; Savale, Laurent; et al.
Aims: To evaluate safety and efficacy of balloon pulmonary angioplasty (BPA) in a large cohort of patients with chronic thromboembolic pulmonary hypertension (CTEPH). Methods: From 2014 to 2017, 184 inoperable CTEPH patients underwent 1006 BPA sessions. Safety and efficacy during the first 21 months (initial period) were compared with those of the last 21 months (recent period). A total of 154 patients had a full evaluation after a median duration of 6.1 months. Results: Overall, there was a significant improvement in New York Heart Association functional class, 6-min walk distance (mean change +45 m), and a significant decrease in mean pulmonary artery pressure (PAP) and in pulmonary vascular resistance (PVR) by 26% and 43%, respectively. The percentage decreases of mean PAP and PVR were 22% and 37% in the initial period versus 30% and 49% in the recent period, respectively (p<0.05). The main complications included lung injury, which occurred in 9.1% of 1006 sessions (13.3% in the initial period versus 5.9% in the recent period; p<0.001). Per-patient multivariate analysis revealed that baseline mean PAP and the period during which BPA procedure was performed (recent versus initial period) were the strongest factors related to the occurrence of lung injury. 3-year survival was 95.1%. Conclusion: This study confirms that a refined BPA strategy improves short-term symptoms, exercise capacity and haemodynamics in inoperable CTEPH patients with an acceptable risk–benefit ratio. Safety and efficacy improve over time, underscoring the unavoidable learning curve for this procedure. Refined balloon pulmonary angioplasty improves short-term symptoms, oxygenation, exercise capacity and haemodynamics in inoperable CTEPH patients with an acceptable risk–benefit ratio http://bit.ly/2UjaHhb